Imaging-Guided Micromachines: Towards Intelligent Systems - Qianqian Wang (Micromachines, 2022)
Micromachines with controllable motion, deformation, and collective behaviors provide advanced methods for performing tasks that traditional machines have difficulty completing thanks to the development of small-scale robotics, nanotechnology, biocompatible materials, and imaging techniques [...]